2009
DOI: 10.1016/s2005-2901(09)60073-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Cytotoxicity of the Traditional Indonesian Medicine Tahongai (Kleinhovia hospita L.) Extract

Abstract: We investigated the leaves of Kleinhovia hospita, a plant which has been traditionally used in Indonesia as phytotherapy to cure liver disease, to describe antioxidant materials from plant sources. K. hospita leaves were extracted with methanol and further partitioned into n-hexane, diethyl ether, and ethyl acetate. The antioxidant activity of each fraction and the residue was assessed using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method and their cytotoxicity on HepG2 liver cancer cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 3 publications
1
20
0
5
Order By: Relevance
“…9 250 mm), yielded compound 1 (5 mg, yield 0.00099%, Fig. 1) named kaempferol 3-O-b-D-glucoside or astragalin which was identical with reported data [6].…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…9 250 mm), yielded compound 1 (5 mg, yield 0.00099%, Fig. 1) named kaempferol 3-O-b-D-glucoside or astragalin which was identical with reported data [6].…”
Section: Methodssupporting
confidence: 85%
“…In our previous study, we reported that ethyl acetate fraction showed antioxidant in DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay but not antiproliferation effect on HepG2 cells [6]. In this study, we isolated two compounds from ethyl acetate fraction and evaluated their antioxidant activities using DPPH radical scavenging assay and their antiproliferation effects on HepG2 cells.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…5) was isolated from the roots of C. robustum, which is used as a traditional Chinese medicine to treat external injuries and irregular menses, and showed good scavenging effects against DPPH radicals with an IC 50 value of 39 µM. 58) Furthermore, numerous extracts from TMPs showed marked antioxidant activity, such as Kleinhovia hospita, 59) Orthosiphon stamineus, 60) Anogeissus acuminata, 61) etc.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Indonesia with its wide biodiversities has plenty of resourceful natural materials those should be explored. Previously our team reported several potential extracts derived from plants including Ipomea batatas (1)(2)(3), Artocarpus altilis (4), Piper crocatum (5), Kleinhovia hospita (6), Artocarpus heterophyllus (7), Catharanthus roseus (8), Piper betle (9), Catharanthus roseus (9), Dendrophtoe petandra (9), Curcuma mangga (9), Curcuma longa (10), Ananas comosus (11), Brucea javanica (12,13), Nephelium lappaceum (14), Cucumis melo (15,16), Caesalpinia sappan (17) and Artocarpus elasticus (18). These extracts shows various activities, including osteoclastogenesis inhibition (1-3), apoptosis induction or proliferation Results inhibition on breast cancer cells (4,5,(7)(8)(9), antioxidant (6,14,16,18), proliferation and differentiation induction on stem cell (10,15), and apoptosis induction on human oral squamous cell carcinoma (12,13,16,17).…”
Section: Introductionmentioning
confidence: 99%